World revolution or socialism, community by community, in the Anthropocene?. Issue 7 (10th November 2019) - Sklair, Leslie
ABSTRACT: The idea of a Fifth International has been around for some time and the historical record is not encouraging. We have all been wrestling with the contradictions the Left faces. The transnational capitalist class has taken setbacks in its stride, while the Left flounders almost everywhere. No communist revolution has resulted in the capture of power by the working class. Now we are all confronted by a new, rapidly unfolding ecological crisis, the Anthropocene. I argue that the most effective response is to exit rather than attempt to overthrow capitalism and the hierarchical state by international revolution. Socialists in positions of authority in state institutions and capitalist enterprises can facilitate this process by enacting legislation that helps people to transition to new smaller-scale non-statist social units, such as producer-consumer co-operatives producing their own food and other essential services over time. Mobilizing the ideas of degrowth, anarching, and consumer-producer cooperatives in the digital age, I argue that under Anthropocene conditions democratic socialism is best constructed from the bottom up, community by community, networked in mutually nurturing relationships.